Impact of Israeli Segregation and Annexation Wall on Palestinian biodiversity - Husein, Duaa; Qumsiyeh, Mazin B. (Africana Studia, 2022)
The aim of the Zionist colonization in Palestine is to transform it from a multi-ethnic, multi-cultural, multi-lingual, and multi-religious country into a monolithic society reflecting visions imported from abroad. By definition this entailed building colonial settlements while changing the character of the land and the relation of indigenous people (including creating refugees and destroying villages). Terraces that saved landscape and prevented erosions were even destroyed. In place, western “development was done”. Here we focus on the impact of such a “development”: annexation and segregation (apartheid) walls used as tools to isolate remaining indigenous people from their lands and from their natural resources have produced significant damage to people and nature. This work is a meta-analysis dependent on literature review, the authors’ own observations, and the eight-year experience of the Palestine Institute for Biodiversity and Sustainability, examining biodiversity in Palestine in areas in which the Wall was fully or partially completed. Data on the short-term impact of Wall on the local biodiversity show how wild mammal behaviour, water flows and plant distributions were affected. However, the data also shows need for more long-run studies. Keywords: Conservation, colonialism, ecosystem, Israeli Wall.